What We Didn’t Know a Recipe Could Be: Political Commentary, Machine Learning Models, and the Fluidity of Form in Nineteenth-Century Newspaper Recipes - Avery Blankenship (Journal of Cultural Analytics, 2024)
In this article, I use document embedding models and a training set of nineteenth-century American recipes to build a pipeline classifier for identifying recipes in the broader nineteenth-century newspaper press. The model reveals a much more expansive understanding of the recipe form, which primarily centers around measurement words and prescriptive language rather than a heavily reliance upon the culinary. This fluidity of form allows nineteenth-century writers to harness the recipe form as a tool for political commentary all while no appearing to disrupt the careful divides between the public and domestic spheres. These recipe-adjacent texts, which are both recipe and not, offer a broader picture of short-form political commentary in the nineteenth century which can include genres and forms once thought unable to gestured beyond the confines of the kitchen.